"They try to suppress us, but we should be louder": a qualitative exploration of intimidation in tobacco control - Britta K Matthes; Raouf Alebshehy; Anna B Gilmore (BMC, 2023)
Abstract Background Tobacco control advocates and researchers face powerful opponents who go to great lengths to protect their interests. While threats and attacks are documented in the grey literature, research into intimidation remains scarce. Building on previous exploratory research, this study seeks to offer in-depth insights into experiences of intimidation in the global tobacco control community. Methods Using qualitative description, we conducted a focus group and semi-structured interviews with tobacco control advocates and researchers to explore their experiences, including forms of, and responses to, intimidation, and ways forward. Data were analysed using qualitative content analysis. Results Twenty-nine individuals from across the globe participated in the study. They reported several forms of intimidation including attacks in the media; online harassment; legal threats; non-legal threats, including death threats; Freedom of Information requests; perceived or actual surveillance; as well as burglary and theft. Responses included non-action (i.e. ignoring attacks); withdrawal (i.e. abandoning a project, area or field); defensive adaptation, for example through self-censorship; and offensive measures, including exposing attacks or filing complaints. Responses were shaped by several factors, including type and level of support from within internal and external networks; as well as an individual's mindset, skills and experiences; and state-civil society relations. Participants suggested several measures that could help address intimidation: 1) report and monitor intimidation; 2) (better) prepare individuals through awareness raising and training (e.g. IT security, legal); 3) support those in need through legal advice, a peer-support network and involvement in response; and 4) look beyond tobacco control to learn and build connections. Conclusion Intimidation is a significant challenge to tobacco control that needs urgent attention. This study suggests measures to address intimidation that require commitment from, and collaboration amongst, multiple actors including governments, international organisations, funders, researchers and civil society. Moreover, collective action beyond tobacco control is needed to not only manage but move beyond intimidation.